SLOPE STABILITY ANALYSIS FOR OPTIMIZATION OF COAL DEPOSIT IN THE LOWWALL PIT XYZ AREA PT. KIDECO JAYA AGUNG, BATU SOPANG DISTRICT, PASER REGENCY, EAST KALIMANTAN PROVINCE - Malik, Trynovianti Putri; Supandi,; Wardana, Novandri Kusuma (ReTII, 2021)
Abstract Pit XYZ is one of the Pits at Pt. Kideco Jaya Agung, where there is a lowwall area that has experienced landslides and as the area still has coal deposits, coal sediment optimization will be carried out. In the optimization of coal deposits, it is necessary to do a back analysis to determine the value of geotechnical parameters (cohesion and inner friction angle) so that the value of the safety factor on the actual slope is known and it can provide recommendations for safe and stable geometric designs. This research is conducted using quantitative methods. In the data processing, a back analysis is performed on each section. The analysis of safety factors and recommendations for slope geometry is carried out using the Morgenstern-Price method. The results show the actual slope stability value for section A with FK = 1,090 and section B with FK = 1,082. After obtaining the FK and PK values on the actual slopes, an optimization design was made for each section with FK = 1,025 and FK = 1,032 for section A and B respectively. This optimization design does not meet the criteria so the researcher makes geometric design options for each section, section A has a value of FK = 1.399% and section B has a value of FK = 1.301. Key words: safety factor, optimum geometric design